Cyanosis when head turned to left in an infant with primary ciliary dyskinesia1. Issue 1 (19th March 2012) - Vermeulen, Bas; Haarman, Eric; Rammeloo, Lukas; Hruda, Jaroslav
Abstract A 19‐month‐old boy with primary ciliary dyskinesia (PCD), mirror‐image dextrocardia, situs inversus (SI) totalis suffered from persistent hypoxia. Cyanosis became clinically evident when the child turned the head to the left and resolved after turning the head to the right. Echocardiography demonstrated two superior caval veins; the left sided superior vena cava (SVC) entering the left sided right atrium (RA) and the right sided into the right sided left atrium (LA). Surgical redirection of the right sided caval vein into RA was performed. Pediatr Pulmonol. 2013; 48:88–90. © 2012 Wiley Periodicals, Inc.